African language media
1 online resource
Keywords: "This book outlines how African language media is affected by politics, technology, culture, and the economy and how this media is creatively produced and appropriated by audiences across cultures and contexts. African language media can be considered as a tool for communication, socialization, and community that defines the various identities of indigenous people in Africa. This book shows how vernacular media outlets including radio and television, as well as native formats such as festivals, rituals and dance, can be used to influence all facets of local peoples' experience and understanding of community. The book also explores the relationship between African language media sources and contemporary issues including the digitalization conundrum, peace and conflict resolution, identity formation, hate speech and fake news. Furthermore, it shows how local media can be used for development communication purposes during health and environmental crises. The book includes cases studies demonstrating the uses, experiences and activities related to various forms of media available in African languages. This book will be of interest to scholars in the field of communication and media studies, health and environmental communication, journalism, African studies and anthropology"--